Analysis of students' mathematical literacy skills in TAPPS model learning with metaphorical thinking approach assisted by Class Dojo - Yanto, Muhammad Dwi; Wardono, Wardono (Department of Mathematics, Universitas Negeri Semarang, 2020)
This research aims to describe students' mathematical literacy skills in the Think Aloud Pair Problem Solving learning model with a metaphorical thinking approach assisted by Class Dojo. The research method used in this study is qualitative. The research subjects were selected by purposive sampling technique based on students’ level of mathematical literacy skills. In this study, data were obtained using triangulation of techniques including test methods, interview methods, and observation methods, as well as using triangulation of sources with 6 research subjects consisting of 2 upper-class students, 3 moderate class students, and 1 lower-class student. Qualitative data analysis includes data validity, data reduction, data presentation, and concluding. The results showed that upper-class students were able to master the six components, there are communication, mathematizing, representation, reasoning and argument, devising strategies for solving problems, and using mathematical tools. Moderate class students are quite capable of mastering the five components, there are communication, mathematizing, representation, devising strategies for solving problems, and using mathematical tools. Lower-grade students were able to master the three components well, there are communication, mathematizing, and using symbolic, formal, and technical language, and operations.